2020
DOI: 10.1016/j.nedt.2020.104444
|View full text |Cite
|
Sign up to set email alerts
|

‘She would wash the patients as if she was scrubbing a dirty plate in the sink’: Exploring nursing students experiences of care delivery

Abstract: Please cite this article as: K. Jack, T. Levett-Jones, R. Ion, et al., 'She would wash the patients as if she was scrubbing a dirty plate in the sink': Exploring nursing students experiences of care delivery, Nurse Education Today (2018),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Students emphasized that they experienced death during their lived experiences of EoL care and realized how important nursing care was for the patients hospitalized in these clinics. As expressed in the relevant literature, students also emphasized that they understood the importance of knowledge and skills in nursing care to meet the needs of patients within the scope of holistic care (Jack et al, 2020; Lian et al, 2019; Valen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Students emphasized that they experienced death during their lived experiences of EoL care and realized how important nursing care was for the patients hospitalized in these clinics. As expressed in the relevant literature, students also emphasized that they understood the importance of knowledge and skills in nursing care to meet the needs of patients within the scope of holistic care (Jack et al, 2020; Lian et al, 2019; Valen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The first phase of the study explored students' experiences using an online survey. The survey results, although mainly positive, revealed that students often witness poor and ineffective care practices during their clinical placements (Jack et al, 2020). The second phase of the study further explored students' perceptions and experiences using narrative telephone interviews in which students were encouraged to talk in-depth about reporting poor care A convenience sample of 14 female nursing students, aged 18 -45, were recruited from three universities, one in Australia and two in the United Kingdom.…”
Section: Setting and Participantsmentioning
confidence: 99%
“…11(p.ix) There are many reports of RNs' experiences of the clinical supervisor role, discussing the challenges encountered in managing the role. International works [14][15][16] invariably conclude there is a need for further effort in preparing clinical supervisors for their role: a phenomenon generating recent interest in Australia. 6,11,[17][18][19] Thus, actioning this recommendation should now become a priority.…”
Section: Introductionmentioning
confidence: 99%